2012
DOI: 10.3233/jad-2012-111346
|View full text |Cite
|
Sign up to set email alerts
|

Deferiprone Reduces Amyloid-β and Tau Phosphorylation Levels but not Reactive Oxygen Species Generation in Hippocampus of Rabbits Fed a Cholesterol-Enriched Diet

Abstract: Accumulation of amyloid-β (Aβ) peptide and the hyperphosphorylation of tau protein are major hallmarks of Alzheimer’s disease (AD). The causes of AD are not well known but a number of environmental and dietary factors are suggested to increase the risk of developing AD. Additionally, altered metabolism of iron may have a role in the pathogenesis of AD. We have previously demonstrated that cholesterol-enriched diet causes AD-like pathology with iron deposition in rabbit brain. However, the extent to which chela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 79 publications
1
42
0
Order By: Relevance
“…In animal models of Parkinson's disease, it has been shown to improve motor performance (Aguirre et al, ; Ayton, Lei, Duce, et al, ; Ayton, Lei, et al, ; Devos et al, ; Dexter et al, ; Workman et al, ). Deferiprone is neuroprotective in neuronal culture models of Aβ toxicity (Molina‐Holgado, Gaeta, Francis, Williams, & Hider, ; Part et al, ), and it has been shown to reduce Aβ burden and tau phosphorylation in a rabbit model of AD (Prasanthi et al, ). Deferiprone was shown to lower brain iron levels (as assessed by MRI and CSF ferritin) and improve motor performance in a Phase 2 study of Parkinson's disease (Devos et al, ), and there is now a Phase 2 study underway for AD (clinicaltrials.gov identifier: NCT03234686).…”
Section: Therapeutically Targeting Iron and Ferroptosis In Admentioning
confidence: 99%
See 1 more Smart Citation
“…In animal models of Parkinson's disease, it has been shown to improve motor performance (Aguirre et al, ; Ayton, Lei, Duce, et al, ; Ayton, Lei, et al, ; Devos et al, ; Dexter et al, ; Workman et al, ). Deferiprone is neuroprotective in neuronal culture models of Aβ toxicity (Molina‐Holgado, Gaeta, Francis, Williams, & Hider, ; Part et al, ), and it has been shown to reduce Aβ burden and tau phosphorylation in a rabbit model of AD (Prasanthi et al, ). Deferiprone was shown to lower brain iron levels (as assessed by MRI and CSF ferritin) and improve motor performance in a Phase 2 study of Parkinson's disease (Devos et al, ), and there is now a Phase 2 study underway for AD (clinicaltrials.gov identifier: NCT03234686).…”
Section: Therapeutically Targeting Iron and Ferroptosis In Admentioning
confidence: 99%
“…In animal models of Parkinson's disease, it has been shown to improve motor performance (Aguirre et al, 2015;Ayton, Lei, Duce, et al, 2013;Ayton, Lei, et al, 2015;Devos et al, 2014;Dexter et al, 2011;Workman et al, 2015). Deferiprone is neuroprotective in neuronal culture models of Aβ toxicity (Molina-Holgado, Gaeta, Francis, Williams, & Hider, 2008;Part et al, 2015), and it has been shown to reduce Aβ burden and tau phosphorylation in a rabbit model of AD (Prasanthi et al, 2012).…”
Section: Ironmentioning
confidence: 99%
“…The scientists suggested that cholesterol-enriched diet may increase body iron deposition that may lead AD. Administering various metal chelators that will help prevent free radical reactions could be helpful in treating the disease [8,121,122]. Curcumin was found to have a high binding affinity for iron and copper, that may work as an iron chelator in AD [123,124].…”
Section: Turmeric and Saffronmentioning
confidence: 99%
“…Although the pathogenesis of the disease is still not fully understood there is a growing consensus that behind the complex molecular mechanism appears to be the accumulation and aggregation of protein fragments. Amyloid-Beta (Aβ), known as amyloid plaques on the blood vessels and the accumulation of intracellular neurofibrillary tangles (tau) that block neurotransmitters and alter metabolism of iron, cause the destruction of nerve cells that accompanies Alzheimer’s [5,6,7,8,9,10,11,12]. It is reported that increased Aβ levels in AD patients reduce plasmalogen levels [13], increase the formation of reactive oxidative species, and slowly obstruct cerebral function [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…High cholesterol diet‐induced AD animal model can be applied to study the relationship between lipid metabolism disorders and AD pathological progress. However, the pathology of hyperphosphorylated Tau protein seldom occurred in the animal models fed with a high‐cholesterol high‐fat diet . The reason for the difference might be that the animals with inappropriate age have been employed in this model.…”
Section: Metabolic Damage Modelsmentioning
confidence: 99%